Architectural design symbolism Catholic Church of Saint Peter and the Virgin Mary Catholic Church Santa Grief Seven in Bandung - Meielisa Chrisylla (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2016)
As a place of holy worship, a Catholic Church should posses a sacred interior and exterior expression. Modernization has caused a good deal of this sacred expression of the Catholic Church to fade. As Catholic Church is a place of worship that supports all liturgical activities, semiotic theory are used to analyze and decipher its architecture to preserve sacredness. The research methodology that was employed was qualitative methods using Peirce’s semiotic principles and their implementation in Church architecture. The principle was then used to analyze two case studies in every detail of their draw up. The area of planning encompassed: (1) Scope of the surrounding environment; (2) Scope of the site; (3) Scope of the form. This analysis employed semiotic principles that were elaborated with Catholic Church principles to create a guideline in the architectural planning of a Catholic Church. The purpose of this research is to find the most dominant sacral expression between Santo Petrus Church and the Santa Perawan Maria Tujuh Kedukaan Church by means of the symbols attached to the architectural elements between these two Catholic Churches.